1986
DOI: 10.1128/iai.54.3.742-750.1986
|View full text |Cite
|
Sign up to set email alerts
|

Binding of purified and radioiodinated capsular polysaccharides from Cryptococcus neoformans serotype A strains to capsule-free mutants

Abstract: Strains 6, 15, 98, 110, and 145 of Cryptococcus neoformans serotype A vary in capsule size, animal virulence, and susceptibility to in vitro phagocytosis. The isolated capsular polysaccharides (CPSs) differ in monosaccharide composition ratios and molecular size, as determined by gel filtration. The purpose of this investigation was to characterize the binding of CPSs to capsule-free mutants of C. neoformans and to examine CPSs from these strains for differences in their ability to bind, to determine whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…The observation that acapsular cryptococci can be incubated with purified GXM and washed and acquire a diminished ability to stimulate lymphoproliferation (Table 1) identifies GXM as the capsular component which mediates the suppression. These results confirm similar observations by ourselves (39,40,43) and others (5,26). A role for GXM in the suppressive phenomenon is further supported by our more recent study which found that anti-GXM MAbs are able to upregulate APC function of monocytes treated with encapsulated cryptococci (44).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observation that acapsular cryptococci can be incubated with purified GXM and washed and acquire a diminished ability to stimulate lymphoproliferation (Table 1) identifies GXM as the capsular component which mediates the suppression. These results confirm similar observations by ourselves (39,40,43) and others (5,26). A role for GXM in the suppressive phenomenon is further supported by our more recent study which found that anti-GXM MAbs are able to upregulate APC function of monocytes treated with encapsulated cryptococci (44).…”
Section: Discussionsupporting
confidence: 92%
“…Incubation of acapsular cryptococci with purified GXM leads to binding of GXM to the yeast surface (14,16,40) and…”
Section: Resultsmentioning
confidence: 99%
“…If it is assumed that IL-1␤ secretion is a response to phagocytosis of the acapsular yeast cells, there is a strong possibility that GXM acts by inhibiting phagocytosis of the yeast. Addition of purified GXM to acapsular cryptococci leads to binding of polysaccharide to the cells (16,34), with a consequent inhibition of phagocytosis (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments that demonstrate high-affinity binding of shed capsule polysaccharides to acapsular cells suggest that a saturable binding process may occur (Kozel and Hermerath, 1984;Small and Mitchell, 1986), but details of this association have not been established. Displacement of pre-existing capsule may contribute to the observed constitutive shedding of capsule into the surrounding environment, whether that is culture medium or the tissues and body fluids of an infected animal.…”
Section: New Capsule On Parental Cellsmentioning
confidence: 99%
“…Alternatively, capsule components shed or secreted from the cell could diffuse outwards and associate with distal parts of the structure. This model (II) is suggested by experiments showing that capsular polysaccharide purified from culture medium can bind to acapsular mutants of Cryptococcus (Kozel, 1977;Kozel and Hermerath, 1984;Small and Mitchell, 1986). Lastly, new material may be interspersed with old (model III), or a combination of these scenarios might occur.…”
Section: Introductionmentioning
confidence: 99%